Hermeneutics of Shamanic Videogames: the Example of “Kisima Inŋitchuŋa” - Maro Y. Malenko (Галактика медиа: журнал медиа исследований)
The article focuses on “ethnological video games”, defined as video games which are developed on the basis of ethnographic and folkloric material. The particular focus is on the kind of ethnological games which contain representation or simulation of shamanistic practices. Among them are Mooseman based on Komi-Permyak and Finno-Ugric mythology, Never Alone based on Iñupiaq folklore, and the rhythm game Nishan Shaman based on a Manchu folktale. The starting point of discussion is: in what cases these kinds of videogames are able to draw players into shamanic or animistic practices, as well as into corresponding ontologies? In order to address this, the article offers a structural-semiotic and ludohermeneutic analysis for one of the above-mentioned games, Never Alone, or Kisima Inŋitchuŋa in Iñupiaq. Using Donna Haraway's concept of “world games”, the article proposes a number of modes of compatibility between video game ontologies and ethnographically identified shamanic ontologies. Correspondence between mythological and video game realities is considered, on the level of performative engagement in the semiotics of a myth or a video game. In its exaggerated form, the question of the article is: how does a playthrough of a “shamanic video game” could be similar to an actual shamanic ritual?